Membrane progesterone receptors in human regulatory T cells: a reality in pregnancy. (2nd February 2015) - Areia, A; Vale‐Pereira, S; Alves, V; Rodrigues‐Santos, P; Moura, P; Mota‐Pinto, A
<x xml:space="preserve">Abstract</x> Objective To provide evidence of the existence of membrane progesterone receptor alpha (mPRα) on regulatory T cells (Treg) in peripheral blood during pregnancy, postulating a possible explanation for the effect of progesterone on preterm birth. Design Cross‐sectional study. Setting Tertiary Obstetric Department in a University Hospital. Population Healthy pregnant women. Methods Treg cells from peripheral blood samples were studied by flow cytometry using multiple monoclonal antibody expression. Main outcome measures Evaluate the number and percentage of CD4+CD25highCD127low, the number and percentage of Treg cells among the total CD4+ T cells, and the percentage and mean fluorescence intensity (MFI) of mPRα in that population, using several gating strategies. Results 43 peripheral blood samples were collected from healthy women during pregnancy, whose median gestational age was 28.7 ± 7.1 (16–40) weeks. The percentage of CD4+ in the total lymphocytes was 43% (32–51) and the percentage of CD4+CD25highCD127low was 4.8% (1.6–5.9), with only 45% (16–72) of those cells expressing the intracellular marker FoxP3 (Treg cell pool). We confirmed the existence of mPRα in that specific population because 8.0% (2.02–33) of the Treg cells were marked with the specific monoclonal antibody, with an mPRα+ MFI of 719 (590–1471). Conclusions This research shows that Treg cells express mPRα during pregnancy, which might play an important role in immune modulation by progesterone.